Cyclic DNA codes over the ring F2+uF2+vF2+uvF2+v2F2+uv2F2 - Dinh H. (2017)
© 2017 Springer Science+Business Media, LLC We study the structure of cyclic DNA codes of odd length over the finite commutative ring (Formula presented.), which plays an important role in genetics, bioengineering and DNA computing. A direct link between the elements of the ring R and 64 codons used in the amino acids of living organisms is established by introducing a Gray map from R to (Formula presented.). The reversible and the reversible-complement codes over R are investigated. We also discuss the binary image of the cyclic DNA codes over R. Among others, some examples of DNA codes obtained via Gray map are provided.